Tourism Communication Strategy Model In Revitalizing Local Culture In Biak Numfor Papua - sudi, Mohamad (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of this study is to determine the collaboration model of tourism communication strategies in revitalizing local culture in Biak Numfor Papua Regency. This research is a descriptive research with a qualitative approach. The data collection method used is the triangulation method by combining data collection techniques such as observation, in-depth interviews, and FGDs to analyze the potential for local culture-based tourism development. The results showed that the collaboration model Strategy applied to revitalize local culture in Biak Numfor Papua in implementing tourism communication programs related to the form of collaboration between actors in tourism industry development policies in Biak Numfor Papua which includes the role of the government, the role of the community, the role of the private sector, the role of the media, and the role of academics who contribute and play an active role in the development process of the tourism sector. In relation to determining tourism communication strategies in revitalizing local culture in Biak Numfor Papua, establishing complementary components in the success of collaboration, including interdependence, constructive unification of thoughts to reach solutions, making decisions with all actors (Joint Ownership of Decisions) , and the existence of joint responsibility as a form of involvement that cannot run between actors if there is no cooperation and support from other factors